Indonesia–Malaysia Export-Import and Islamic Economic Growth - Devy Septi Heryani; Nurheti Nurheti (Penerbit Goodwood, 2026)
Purpose: This study analyzes the contribution of exports and imports to Gross Domestic Product (GDP) from an Islamic economics perspective, using a comparative study between Indonesia and Malaysia (2019–2024). Methodology/approach: A quantitative approach using panel data regression analyzes annual secondary data from BPS, DOSM, and the World Bank through OLS, FEM, and REM, with the best model determined by the Hausman test. Results/findings: The study finds that exports and imports together significantly affect national income in both countries. The Random Effects Model (REM) is the most suitable, with an R² of 0.997. From an Islamic economic perspective, halal and productive exports are commendable as they reflect maslahah and ikhtiar, while productive imports are permissible but consumption-driven imports should be regulated to maintain istiqlal (economic independence). Conclusions: Simultaneous export and import activities significantly affect both countries’ national income, though individually insignificant. In Islamic economics, productive exports are encouraged, and productive imports are allowed as long as they do not undermine the ummah’s economic independence. Limitations: The study spans six years and two countries, limiting analytical significance, and excludes key variables such as investment, fiscal policy, and political stability. Contribution: This study enriches the literature by integrating empirical trade analysis with Islamic principles, providing insights for policymakers to develop value-based trade strategies that foster ethical growth and economic sovereignty.